Thermal dissociation of diatomics in inert gases: A Nosé equation approach - Hamilton, I. P.; Liu, L. (The Journal of chemical physics, 1990)
The thermal dissociation of diatomics in inert gases has been the subject of numerous experimental and theoretical studies. There is excellent agreement between the measured and calculated bimolecular rate constants for H2, and this has become a test case for master-equation and other approaches. In this paper we consider a Nosé equation approach, which is appropriate if the inert gas simply acts as a heat bath, as may be the case in the limit of infinite dilution of H2. We examine the extent to which the Nosé equation can thermalize the H2 dynamics for the temperature range 4000–10 000 K. We show that we can calculate meaningful pseudo-unimolecular rate constants for the temperature range 7000–10 000 K and, for this temperature range, we obtain an activation energy of 3.7±0.5 eV, which is compatible with the experimental value.